Hardcore research : punk, practice, politics - Butz, Konstantin; Winkler, Robert A. (Culture & theory ;, 2023)
For more than 40 years, hardcore and punk have promised to offer an alternative to what is perceived as the norm and as mainstream. Hardcore Research: Punk, Practice, Politics provides a comprehensive insight into the most active, outspoken, and widely received scholarly positions in the academic discourses on hardcore and punk and combines them with a variety of new and emerging voices. The book brings together scholars with personal ties to past and present hardcore and punk scenes, who present both insightful and critical examinations of the rich and varied histories of this subcultural phenomenon and its current reverberations at the intersection of cultural practice and academic research.